2021
DOI: 10.1136/tobaccocontrol-2021-056694
|View full text |Cite
|
Sign up to set email alerts
|

Was the implementation of standardised tobacco packaging legislation in England associated with changes in smoking prevalence? A segmented regression analysis between 2006 and 2019

Abstract: Background and aimIn 2016, England initiated the implementation of standardised tobacco packaging, introduced in conjunction with minimum pack sizes and other measures included in the 2014 European Tobacco Products Directive, over the course of a 1-year sell-off period ending in May 2017. These measures have been shown to have been associated with increases in tobacco prices and product diversity. We now investigate the association between implementation of the new legislation and smoking status in England.Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…We used a diverging approach for this research question because we assumed that the introduction of Standardised Packaging of Tobacco Products Regulations may have been more likely to cause a step change in the decline in the rate of current smoking among 16-24-year-olds at the beginning of the introduction than a gradual change. This approach is in line with findings from Opazo Breton et al 7 who found a significant change in the level but not the slope of the odds of smoking, starting after the introduction of the policy in May 2016.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We used a diverging approach for this research question because we assumed that the introduction of Standardised Packaging of Tobacco Products Regulations may have been more likely to cause a step change in the decline in the rate of current smoking among 16-24-year-olds at the beginning of the introduction than a gradual change. This approach is in line with findings from Opazo Breton et al 7 who found a significant change in the level but not the slope of the odds of smoking, starting after the introduction of the policy in May 2016.…”
Section: Discussionsupporting
confidence: 91%
“…Second, we modelled the effect of the intervention as a gradual level shift from June 2016 until May 2017 (ie, a year earlier than our primary analysis; coded 0 up to May 2016, then increasing by 1/12 until May 2017 and coded 1 from then onwards) because, even though our primary hypothesis was that the policy took effect once the grace period for tobacco manufacturers had past and it was fully implemented, we additionally wanted to test a potential effect starting at the time the policy was first implemented (beginning of the grace period), as was found by research assessing the policy's impact on smoking prevalence. 7 Third, we modelled trends in mean daily cigarette consumption for those exclusively (rather than predominantly, as in our primary analysis) smoking FM and RYO cigarettes, respectively. Finally, we calculated Bayes factors (using an online calculator, 21 results presented in the online supplemental file) to test whether there was evidence for the null hypothesis of no difference or if the data were insensitive to detect an effect corresponding to an increase in mean daily cigarette consumption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight EU MS (including at that time the UK) went beyond the TPD’s minimum labelling provisions and introduced plain packaging for tobacco products,26 leading to the development of a regional evidence base in support of plain packaging. Based on evidence from EU MS, plain packaging along with pictorial warnings appear to increase awareness of tobacco-related diseases, making warnings more salient and supporting reductions in smoking 27–29. More recent evidence also indicates that about half of the EU population supports the adoption of plain packaging, however with significant cross-country differences (ranging from 72% in Ireland and the UK, 66% in Belgium to 28% in Portugal) 30…”
Section: Main Textmentioning
confidence: 99%
“…In addition, we ran a sensitivity analysis varying the date of the tobacco products directive to the end date of the implementation period (May 2017). 34 …”
Section: Methodsmentioning
confidence: 99%